2006
DOI: 10.1038/nmat1558
|View full text |Cite
|
Sign up to set email alerts
|

Chiral switching by spontaneous conformational change in adsorbed organic molecules

Abstract: Self-assembly of adsorbed organic molecules is a promising route towards functional surface nano-architectures, and our understanding of associated dynamic processes has been significantly advanced by several scanning tunnelling microscopy (STM) investigations. Intramolecular degrees of freedom are widely accepted to influence ordering of complex adsorbates, but although molecular conformation has been identified and even manipulated by STM, the detailed dynamics of spontaneous conformational change in adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
205
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(228 citation statements)
references
References 25 publications
20
205
0
3
Order By: Relevance
“…Such a case has been observed for prochiral bis-ethynyl-p-phenylene compounds on Au(111) (Fig. 30) [210]. Besides the two enantiomers, an achiral meso-form exists at the surface.…”
Section: Diastereomers and Diastereomeric Recognitionmentioning
confidence: 55%
“…Such a case has been observed for prochiral bis-ethynyl-p-phenylene compounds on Au(111) (Fig. 30) [210]. Besides the two enantiomers, an achiral meso-form exists at the surface.…”
Section: Diastereomers and Diastereomeric Recognitionmentioning
confidence: 55%
“…This rate is related to the energy barrier E associated with the conformational change by the Arrhenius equation k f ) k 0 exp(-E/k B T), where k B is the Boltzmann constant. Assuming a value of 10 11 -10 12 s -1 for the prefactor k 0 (consistent with the attempt frequency associated with a relatively soft phonon mode 40 ), the energy barrier E can be estimated to be about 0.8 eV. This value is possibly overestimated because of undersampling, as some more switching events may have been missed as a result of our limited image acquisition rate.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, the operation of catalysts and enzymes depends on understanding how particular molecules react with surface catalytic sites. [15][16][17] The manner in which molecules engage with and ultimately dock at these surface sites is critically important. In these and related systems, numerous studies have reported on the final state properties, that is, after the contact has been assembled or the reaction completed.…”
Section: Introductionmentioning
confidence: 99%